PENGARUH KEPEMIMPINAN, KOMPETENSI DAN TEAM WORK TERHADAP PRESTASI KERJA PEGAWAI PADA PT. AGRINDO - GRESIK - jurnalpps pps; Arief Budiman; Martinus Rukismono (Jurnal Manajerial Bisnis, 2022)
The quality of human resources is the most important element in improving good and high quality corporate governance. To create high performance requires a firm leadership attitude in managing human resources who have competence in carrying out work and solid teamwork to achieve organizational goals. Research to examine the influence of leadership, competence and team work on the work performance of employees of PT. AGRINDO. The results of the research show that leadership, competence, team-work affect the work performance of PT. AGRINDO. Competence has a dominant influence on the work performance of employees of PT. AGRINDO.